Pengaruh Kompensasi dan Kualitas Pelayanan terhadap Kinerja Pegawai di Dinas Perumahan Rakyat dan Kawasan Pemukiman (PRKP) Kabupaten Karawang - Orce Kabunggul; Mohamamd Makbul; Muh. Alfian (Journal of Law and Administrative Science, 2024)
This research at the Public Housing and Settlement Area Service (PRKP) Karawang Regency,Identification of research problems Compensation is not in accordance with performance. (X1), servicequality has not met expectations. (X2), Inadequate facilities and infrastructure. (X2), Have not reachedstandardization of performance. (Y) and Less Effective Employee Performance. (Y) so the problem iswhether there is an effect of salary levels and employee performance on service quality at the PublicHousing and Settlement Area Service (PRKP) Karawang Regency, then the benefits for postgraduatestudents can be used as a reference for further research. Employee Salaries and Performance on ServiceQuality at the Public Housing and Settlement Area Office (PRKP) of Karawang Regency. Quantitativeresearch methods by observation and distributing online questionnaires to respondents, Data Analysis byCollecting data on the first Primary and secondary model analysis, Data reduction, Data presentation,Drawing conclusions. combined the two indicators in accordance with the hypothesis. In this test, it can beseen that Compensation (XI) and Service Quality (X2) have a significant effect on Employee Performance.Based on the conclusions and consequences described, the author intends to improve the compensationvariable X1 and Service Quality Variable (X2) if you want to increase employee performance variable (Y).